Peningkatan Karakter Islami Anak Melalui Buku Digital Pintar - Izharsyah, Jehan Ridho; Mahardika, Ananda; Syafruddin, Syafruddin; Az-zahra, Ayasha Sofya (Universitas Muhammadiyah Mataram, 2025)
Abstract: The kids come from low-income families and have less education overall. Additionally, some students have physical restrictions that make it challenging for class supervisors and teachers to adjust to their personalities. The purpose of this service is to support and strengthen instructors' teaching strategies and children's Islamic character.The approach uses the smart digital book